2011
DOI: 10.1007/s00103-010-1205-x
|View full text |Cite
|
Sign up to set email alerts
|

Wer wählt den Hausarzt zum „Gatekeeper“?

Abstract: Since July 2009, statutory health insurance companies in Germany are obliged to offer a so-called general practitioner model. By strengthening the general practitioner's position, these models should optimize healthcare especially for people with higher demands for health services. So far, little is known about which patients participate in the model. Our study's aim was to describe correlates of enrollment based on the behavioral model of health services use. The data were obtained from the Robert Koch Instit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 11 publications
1
5
1
2
Order By: Relevance
“…The age effect could not be clearly determined by our study because, depending on the statistical model, there was at times a correlation and then again no correlation with the commitment to the GP. The presence of medically diagnosed conditions and belonging to the social middle and lower class are linked to more willingness to participate in HzV [10]. The results of our investigation imply similar correlations with the commitment to the GP.…”
Section: Comparison With Literature and Discussion Of Resultssupporting
confidence: 72%
See 3 more Smart Citations
“…The age effect could not be clearly determined by our study because, depending on the statistical model, there was at times a correlation and then again no correlation with the commitment to the GP. The presence of medically diagnosed conditions and belonging to the social middle and lower class are linked to more willingness to participate in HzV [10]. The results of our investigation imply similar correlations with the commitment to the GP.…”
Section: Comparison With Literature and Discussion Of Resultssupporting
confidence: 72%
“…Vice versa, our study revealed higher commitment to the GP for patients from rural areas. Investigations of the HzV in Germany by Schnitzer et al and Kürschner et al report that older patients or retirees participate more often in GP models [10,11]. The age effect could not be clearly determined by our study because, depending on the statistical model, there was at times a correlation and then again no correlation with the commitment to the GP.…”
Section: Comparison With Literature and Discussion Of Resultscontrasting
confidence: 70%
See 2 more Smart Citations
“… 10 GPs are more frequently consulted by patients who are elderly (>65 years), female, non-smokers, not economically active and have lower social status, higher morbidity and a poorer health-related quality of life. Kürschner et al 11 showed that the main indicators for enrolment in a general practitioner care model, where coordination of healthcare use is provided solely by GPs, were age above 60, lower social status, lower income status and residence in less populated areas.…”
Section: Introductionmentioning
confidence: 99%